Islamic law in context a primary source reader - Anchassi, Omar 1988-; Gleave, R. (Robert) (New York Cambridge University Press, 2024)
This volume surveys the diversity of Islamic legal thought and practice, a 1500 - year tradition that has been cultivated throughout the Islamic world. It features translations of Islamic legal texts from across the spectrum of literary genres (including legal theory, judicial handbooks, pamphlets) that represent the range of temporal, geographic and linguistic contexts in which Islamic law has been, and continues to be, developed. Each text has been chosen and translated by a specialist. It is accompanied by an accessible introduction that places the author and text in historical and legal contexts and explains the state of the relevant field of study. An introduction to each section offers an overview of the genre and provides a useful bibliography. The volume will enable all researchers of Islamic law - established academics, undergraduate students, and general readers -- to understand the tremendous and sometimes bewildering diversity of Islamic law, as well the continuities and common features that bind it together
Includes bibliographical references and index.
Keywords: Islamic law; Islamic law. -- Commentaries